Intelligence Location Detection Line Following Robot using RFID System - Mustaffa, Syafiqah; Roslan, Hazli (Progress in Engineering Application and Technology, 2021)
In this era of globalization, the rapid development of science and technology has made Malaysia a country that has a high demand for the manufacturer from our industry. This makes the need of labour increased and it will require a high cost when there has an increase in the number of employees. For an industry that requires human resources to transfer items from one place to another, an equipment that can replace human resources and can work on its own is necessary. Therefore, a device called “Intelligence Automatic Driven Drawer (IADD)” is designed as an alternative to handle this problem. This equipment operates automatically using several sensors, DC motor and microcontrollers. The sensors used are Infrared Sensor as a movement guide, Ultrasonic Sensor as barrier detector and Radio Frequency Identification (RFID) system as a location detector. While microcontroller used is Arduino as the controller of the entire system and as the connecter for all equipment. This tool operates using a rechargeable battery power supply and moves itself to the charging point when the power is reduced according to the setting set. This equipment can carry a light load and move according to the black line that the user sets as a movement guide. This tool will function as long as the power supply is not disconnected.